PENANAMAN SIKAP MODERASI BERAGAMA DI SMP NEGERI 3 ABIANSEMAL - Ni Putu Jeni Astari; I Ketut Tanu; I Gde Suryawan (JAPAM (Jurnal Pendidikan Agama), 2024)
Religious moderation is described as an effort to follow and maintain religious principles, turning them into a way of life and character, so that religious moderation can foster an attitude of tolerance and maintain harmony between religious communities. Religious moderation has the potential to grow and develop in the school environment, where education cannot be separated from the teacher's ability to convey learning and information to students. Teachers have an important role in directing and building religious moderation in schools. The formulation of the problem in this research is: 1) Which attitudes of religious moderation can be instilled in students at SMPN 3 Abiansemal, 2) What are the obstacles faced in the process of instilling attitudes of religious moderation in students at SMPN 3 Abiansemal, 3) What is the impact of instilling an Attitude of Religious Moderation in Students at SMPN 3 Abiansemal. The theories used to analyze this problem are constructivism theory, humanistic theory and behavioristic theory. Data collection methods use observation, interviews, literature study and documentation. The collected data was analyzed using qualitative descriptive data analysis techniques. The results of this research show: 1) an attitude of religious moderation has been given to students starting from the Introduction to the School Environment (MPLS) period. The attitudes of religious moderation that are instilled in students at SMPN 3 Abiansemal refer to the four indicators of religious moderation. Apart from that, teachers also instill attitudes of religious moderation through the application of the Tri Hita Karana teachings in life. 2) There are several inhibiting factors, namely, first there are environmental factors, factors influencing the use of social media, and finally there are students' lack of interest in reading. 3) There are positive and negative impacts from efforts to instill attitudes of religious moderation in students at SMPN 3 Abiansemal.